Rural basic service development: An Operational Approach - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1991)
Approach on the study or rural service development is often both development indicators are interchangeable. However, the two studies are closely related and could contribute one to another. A confusion also exists in the setting up of the concepts of social service and economic service function. As such, the study of service development should have a great care of the study implication in which sectoral action planning should follow-up.